The Implementation of Religious Moderation in Jesuit High Schools in Indonesia: Catholic Religious Education Teachers’ Perspectives - Alexander Hendra Dwi Asmara (Fakultas Teologi, Universitas Sanata Dharma, 2024)
The implementation of “Religious Moderation” has been the priority of the Indonesian government since its official introduction by the Ministry of Religious Affair in 2019. From Catholic perspective, religious moderation is perceived as the Church’s openness to build culture of engagement indicated by the willingness to build dialogue and collaboration to promote social justice, morality, freedom, and peace. Religious moderation is in line with Pope Francis’ latest encyclic of Fratelli Tutti where all people are called to work together for the common good. Nevertheless, the implementation of religious moderation has raised several questions, particularly on how this vision can be put into practice in school context. Every school has different contexts which needs to be considered in applying religious moderation. Based on this concern, this research wants to focus on the teacher’s implementation of religious moderation in the context of Catholic religious education. The researcher chose religious teachers considering that religious moderation should give deeper impact on the learning process for faith formation. This research also pay attention to Jesuit education. Jesuit education is focused on creating “school of dialogue”, a model of Jesuit education that is centered at Catholic values and traditions, and at the same time, being aware of its position in the midst of religious plurality. This study is qualitative. The data were gathered through questionnaires that contain both closed-ended and open-ended questions. The participants of this study were 17 Catholic religious education teachers from six Jesuit High Schools in Indonesia. The data were gathered first in May to July 2022, but then the researcher continue to elaborate dan deepen the data from November to December 2023.